Expert Systems in Foreign Language Training and Learning - Kseniya Sukhikh; Svetlana, Menshenina (Cakrawala: Jurnal Pendidikan, 2025)
This paper examines the integration of expert systems in foreign language learning through a systematic literature review. Drawing from theories such as TPACK, Constructivism, and CALL, the study analyzes key features, methodologies, and applications of expert systems. It also addresses ethical considerations and socio-cultural diversity. Findings suggest that expert systems offer adaptive, individualized, and engaging approaches, but challenges remain regarding structure, access, and user dependency.